2019
DOI: 10.1017/s1355617719000079
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Early Childhood Resilience Following Neonatal Brain Injury From Parents’ Perspectives Using a Mixed-Method Design

Abstract: Objectives: The current study used a mixed-method design to qualitatively examine parents’ definitions of resilience and factors they believed optimized their child’s early outcome following neonatal brain injury. This was followed by quantitative analyses of early developmental and mental health outcomes and their relation to salient biopsychosocial factors. Methods: Participants were parents of children diagnosed with neonatal brain injury due to stroke or hypoxic-ischemic encephalopathy (N=51; age range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Although re/habilitative services are typically available at the time of diagnosis, many neurocognitive challenges persist or worsen, particularly as demands for independent functioning increase with age. Considerable evidence suggests that the behavioral health care needs of children and adolescents with ABI go unmet, with parents and schools struggling to adequately support these children (Nicklin et al, 2019;Williams et al, 2019). Before delving further into considerations around intervention and the surrounding context, it is important to distinguish between rehabilitation and habilitation.…”
Section: What the Field Knowsmentioning
confidence: 99%
“…Although re/habilitative services are typically available at the time of diagnosis, many neurocognitive challenges persist or worsen, particularly as demands for independent functioning increase with age. Considerable evidence suggests that the behavioral health care needs of children and adolescents with ABI go unmet, with parents and schools struggling to adequately support these children (Nicklin et al, 2019;Williams et al, 2019). Before delving further into considerations around intervention and the surrounding context, it is important to distinguish between rehabilitation and habilitation.…”
Section: What the Field Knowsmentioning
confidence: 99%
“…Good family functioning [ 4 ] also facilitates recovery from childhood stroke. Parents reported that treating the child as “normal” aided recovery [ 14 ]. A supportive social network, from close family and friends [ 14 ] to the wider society [ 13 ], is important for both parents and children to facilitate recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Clear communication with parents by medical professionals about the causes of the stroke and events occurring around the stroke has been identified as an important issue [ 4 ]. Patients have appreciated positivity from clinicians [ 14 ], close and ongoing medical support [ 14 , 15 ], involvement with goal-setting approaches [ 16 , 17 ], and continuity of care. There is limited medical awareness or literature to support parents during their child’s recovery from stroke [ 2 , 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…That same meta-analysis demonstrated a positive association of structure and responsivity with cognitive outcomes. Qualitatively, caregivers have identified addressing their children's mental health and behavioural challenges as central to optimizing their child's and family's overall well-being (Williams et al, 2019). Thus, parenting behaviours may be a modifiable pathway to improve both child and caregiver mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%